The essence of the organization of lessons in subjects in HEIs (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Organization of classes in universities also includes coordination of teachers' work, distribution of study load, consultations and conducting individual classes with students. It is based on the principles of systematicity, consistency and expediency, aimed at forming students' competences, skills and abilities, as specialists in their field.